Pengembangan Modul Pendidikan Multikultural Berbasis Karakter Cinta Tanah Air dan Nasionalis pada Pembelajaran Tematik - Laila Fatmawati; Rani Dita Pratiwi; Vera Yuli Erviana (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2018)
This research aims to describe the development steps and the appropriateness of multicultural education module based on the character of patriotism and nationalism in thematic learning for students in 2nd grade Elementary School. This is a research and development applying Borg and Gall design. The trial was conducted on 10 students of 2nd grade in Muhammadiyah Bodon Elementary School. The data collection techniques in this research were interviews, observations, module feasibility assessments by experts, teachers’ assessment, and questionnaire of learners’ responses. The eligibility of the multicultural education module is shown by the result of the assessment by the validation experts at the time of FGD. The validation by media expert scored of 72, the validation by learning expert scored of 74, and the validation by language expert scored of 60. The limited product trial were conducted in class II A, based on the students' assessment get the mean score of 37.5, while the assessment by the teacher scored 70 , both are very good category. The field trial were conducted in class II B, based on the students' score, obtained 36.94 score, and 76 from the teachers; both are very good category.